2018
DOI: 10.3390/en11051184
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Powertrain Electrification and Future Scenarios for Non-Road Mobile Machinery

Abstract: Powertrain electrification continues to be a growing trend in vehicular applications. Electric powertrains have numerous advantages over traditional mechanical and hydraulic powertrains but there are still important challenges to overcome for long-term commercial success. This research presents a technological assessment of present and future developments of powertrain electrification in non-road mobile machinery (NRMM). The challenges and opportunities of NRMM electrification are described in detail. The tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 89 publications
0
59
0
2
Order By: Relevance
“…In recent years, there has been increasing attention paid to the electrification of non-road mobile machinery, focusing on the machinery involved in construction and agricultural applications [1]. The tractor is a wheeled or tracked vehicle used for the traction of agricultural machinery [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been increasing attention paid to the electrification of non-road mobile machinery, focusing on the machinery involved in construction and agricultural applications [1]. The tractor is a wheeled or tracked vehicle used for the traction of agricultural machinery [2].…”
Section: Introductionmentioning
confidence: 99%
“…Compare that with charging or discharging batteries 80% with the efficiency, while electric tractors are more efficient. The adoption of electric machines and battery technologies together with efficient diesel engines or, in some cases, replacing them in full electric configurations can reduce or completely avoid ENGINEERING PERSPECTIVE e-ISSN:2757-9077 https://sciperspective.com/ Research Paper local pollutant emissions [12,13,14]. Electric motors have certain drawbacks, such as charging and the need for costly line extensions [15].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in literature, NRMMs electrification can improve their efficiency [11][12][13][14]. The adoption of electric machines and battery technologies together with efficient diesel engines or, in some cases, replacing them in full electric configurations can reduce or completely avoid local pollutant emissions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Antti Lajunen has identified that the mining ventilation cost is a major cost‐saving factor for clean fuel cell propulsion in addition to its higher energy efficiency, 1 finding the mining vehicles a niche application market for FCEVs. With technology advances, the PEMFC technology is getting more cost‐competitive for off‐road mining trucks 2 . However, the investment cost and service life of PEMFC systems still hinder their wide adoption and commercialization at present.…”
Section: Introductionmentioning
confidence: 99%